1996
DOI: 10.1002/etc.5620150726
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of low levels of chlorsulfuron and other herbicides on growth and yield of nontarget plants

Abstract: Abstract-The influence of low application rates of chlorsulfuron on the growth and reproduction of four taxonomically diverse plant species (canola, smartweed, soybean, and sunflower) were examined. Exposures examined ranged from 1 ϫ 10 Ϫ3 to 8 ϫ 10 Ϫ3 of the recommended field rates for cereal crops and were approximately 1,000 times less than the highest exposure recommended by the U.S. Environmental Protection Agency. Each species received a single application at one of three different stages of reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…Longer-term studies with different endpoints would be needed to determine the overall effect of glyphosate or atrazine on plant performance. Previous studies have found that significant herbicidal effects can become apparent a full year after spray [1,7] and that reproduction can be adversely affected [28,29]. It was evident that some recovery of biomass occurred for both terrestrial and wetland communities treated with atrazine.…”
Section: Discussionmentioning
confidence: 94%
“…Longer-term studies with different endpoints would be needed to determine the overall effect of glyphosate or atrazine on plant performance. Previous studies have found that significant herbicidal effects can become apparent a full year after spray [1,7] and that reproduction can be adversely affected [28,29]. It was evident that some recovery of biomass occurred for both terrestrial and wetland communities treated with atrazine.…”
Section: Discussionmentioning
confidence: 94%
“…Even though in the present study NOEC and EC25 data were compared for plants treated with herbicides at the same chronological age ($14 DAE) for both plants in pots and plants in the field, there is no way to know whether tuber initiation occurred at the same time in the small pots as in the field. In other studies, there was no clear relationship between stage of plant development (preflowering to flowering) and herbicide sensitivity among four plant species [21]. Thus, although young seedling potato plants grown in small pots indicate the potential for effects on tuber production, the amount of reduction in tuber weight in relation to herbicide treatment may be different from the response of field-grown plants.…”
Section: Relationship To Field Potato Responsesmentioning
confidence: 91%
“…The type and texture, % organic carbon, pH and salt content as electronic conductivity of the final prepared soil should be reported. The soil should be classified according to a standard classification scheme (13). The soil could be pasteurized or heat treated in order to reduce the effect of soil pathogens.…”
Section: Description Of the Methodsmentioning
confidence: 99%